Institutional Ownership, Managerial Ownership, and Firm Size as Determinants of Tax Avoidance in Mining Companies - Chelsea Savana Nirwani; Andang Wirawan Setiabudi (Journal of Business and Economics Research (JBE), 2026)
Given the importance of taxation as the primary source of government revenue, the practice of tax avoidance remains a concern, as many companies seek to minimize their tax liabilities through various strategies that remain within the bounds of the law. This study aims to analyze the influence of institutional ownership, managerial ownership, and firm size on tax avoidance among mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. 2024 providing updated empirical evidence amid evolving tax regulations in Indonesia's post-pandemic economic recovery. The study utilizes secondary data obtained from the companies’ annual financial reports during the observation period. The sample was selected using purposive sampling with a quantitative approach and hypothesis testing methods. Data analysis was conducted via multiple linear regression using SPSS software. The results indicate that institutional ownership has a positive effect on tax avoidance. This finding indicates that the presence of institutional ownership has not yet been able to strengthen the company’s oversight function in curbing tax avoidance practices. Meanwhile, managerial ownership and firm size do not influence tax avoidance. These results suggest that the extent of share ownership by management or the size of the firm has not yet become a determining factor in the level of tax avoidance among mining companies listed on the IDX.